Gravidez após Colocação de Banda Gástrica para Tratamento da Obesidade Mórbida - Conde, P (2013)
Obesity is known to have a negative impact on pregnancy outcome, as it is associated with an increase in the incidence of gestational diabetes, hypertension, preeclampsia, neural tube defects, macrosomia, and late fetal death. Gastric banding is considered an appropriate intervention for morbid obesity when other weight-loss measures are unsuccessful, and this treatment has been shown to be effective in causing a sustainable weight loss. Some women will become pregnant after bariatric surgery, and the nutritional and metabolic challenges brought by gastric banding may have a profound impact on maternal health and pregnancy outcome. The authors report the case of a 27 year old pregnant woman, with a past medical history of gastric banding surgery for morbid obesity. At 18 weeks of gestation, the patient started complaining of severe nausea and vomiting, The situation deteriorated three weeks later when she rapidly developed severe desnutrition, dehydration and early signs of liver and renal failure. Migration of the gastric band was diagnosed, and laparoscopy conducted to remove it. In the day following surgery the patient complained of absent fetal movements, and an intrauterine demise was diagnosed on ultrasound. Pathological examination of the fetus and placenta failed to reveal the cause of death, but no growth restriction was documented, suggesting the occurrence of an acute event.